Combination of biochemical and mechanical cues for tendon tissue engineering. Issue 11 (4th May 2017) - Testa, Stefano; Costantini, Marco; Fornetti, Ersilia; Bernardini, Sergio; Trombetta, Marcella; Seliktar, Dror; Cannata, Stefano; Rainer, Alberto; Gargioli, Cesare
Abstract: Tendinopathies negatively affect the life quality of millions of people in occupational and athletic settings, as well as the general population. Tendon healing is a slow process, often with insufficient results to restore complete endurance and functionality of the tissue. Tissue engineering, using tendon progenitors, artificial matrices and bioreactors for mechanical stimulation, could be an important approach for treating rips, fraying and tissue rupture. In our work, C3H10T1/2 murine fibroblast cell line was exposed to a combination of stimuli: a biochemical stimulus provided by Transforming Growth Factor Beta (TGF‐β) and Ascorbic Acid (AA); a three‐dimensional environment represented by PEGylated‐Fibrinogen (PEG‐Fibrinogen) biomimetic matrix; and a mechanical induction exploiting a custom bioreactor applying uniaxial stretching. In vitro analyses by immunofluorescence and mechanical testing revealed that the proposed combined approach favours the organization of a three‐dimensional tissue‐like structure promoting a remarkable arrangement of the cells and the neo‐extracellular matrix, reflecting into enhanced mechanical strength. The proposed method represents a novel approach for tendon tissue engineering, demonstrating how the combined effect of biochemical and mechanical stimuli ameliorates biological and mechanical properties of the artificial tissue compared to those obtained with single inducement.